2019
DOI: 10.1111/pan.13574
|View full text |Cite
|
Sign up to set email alerts
|

Society for the advancement of blood management administrative and clinical standards for patient blood management programs. 4th edition (pediatric version)

Abstract: Summary Patient Blood Management is the timely application of evidence‐based medical and surgical concepts designed to maintain hemoglobin concentration, optimize hemostasis, and minimize blood loss to improve patient outcomes. Conceptually similar to a “bundle” strategy, it is designed to improve clinical care using comprehensive evidence‐based treatment strategies to manage patients with potential or ongoing critical bleeding, bleeding diathesis, critical anemia, and/ or a coagulopathy. Patient Blood Managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 32 publications
0
66
0
5
Order By: Relevance
“…Although the PBM was primarily introduced in the area of adult care, its individual measures may also have had an impact on pediatrics. The treatment of iron deficiency anemia with iron preparations or the use of erythropoietin; reduction of the number and volume of blood samples; and adherence to physiological conditions of hemostasis (pH, calcium concentration and temperature) can be used, as well as the use of bedside coagulation diagnostics and targeted therapy in children [2,[13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Although the PBM was primarily introduced in the area of adult care, its individual measures may also have had an impact on pediatrics. The treatment of iron deficiency anemia with iron preparations or the use of erythropoietin; reduction of the number and volume of blood samples; and adherence to physiological conditions of hemostasis (pH, calcium concentration and temperature) can be used, as well as the use of bedside coagulation diagnostics and targeted therapy in children [2,[13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Patient blood management guidelines and the most recent evidence for transfusion thresholds should be reviewed and implemented 4–8 . Several well controlled, randomized trials have demonstrated the safety of using a restrictive hemoglobin trigger (7‐8 g/dL) for patients in many settings in the hospital 9,10 .…”
Section: Responsementioning
confidence: 99%
“…While some pediatric guidelines exist, the recommendations made for the use of VET are mainly based on the results of single-center retrospective studies and a handful of small randomized studies. 3,6 Although goal-directed bleeding management protocols based on VET are certainly beneficial in the pediatric population and have been favored by many authors, 3,5,7 Abbreviations: CFTs, clot formation times; CPB, cardiopulmonary bypass; CTs, clotting times; EXTEM, extrinsically activated test; FIBTEM, fibrin clot polymerization; INTEM, intrinsically activated test; MA, maximum clot amplitude; MCF, maximum clot firmness; ROTEM, rotational thrombelastometry; TEG, thrombelastography; VET, viscoelastic testing. clear thresholds and targets for neonates and pediatric patients have been poorly defined, and further studies are needed to develop and validate VET-based transfusion algorithms in neonates and children.…”
Section: Introductionmentioning
confidence: 99%